Review of East African Plant Collectors - Byng, James W. (Phytotaxa, 2015)
The Flora of Tropical East Africa, covering Uganda, Kenya and Tanzania, was one of the largest regional floras ever compiled, with over 12,000 wild plant species and taking 64 years to complete. The East African Plant Collectors is the perfect supplement to this great flora and is a wonderful compendium of botanists, collectors and authors showing the human element of the flora - the people behind the herbarium specimens, the new species and combinations and the flora treatments. This book includes around 2,700 collectors that have collected herbarium specimens in the region arranged alphabetically. Each individual entry includes biographical data, including nationality, dates of birth and death, travels, publications, eponymy, publications and it lists the herbaria where specimens were deposited. The level of detail varies considerably from collector to collector with some briefly treated, whilst others are very detailed. For example, Bernard Verdcourt’s entry is lengthy and includes location details of his 30 years of fieldwork, publication details of the flora treatments he compiled (a remarkable one-fifth of the flora...) and even an anecdote about meeting a lion on Ndi Hill!